Levelized cost of electricity for photovoltaic/biogas power plant hybrid system with electrical energy storage degradation costs. (1st December 2017) - Lai, Chun Sing; Jia, Youwei; Xu, Zhao; Lai, Loi Lei; Li, Xuecong; Cao, Jun; McCulloch, Malcolm D.
Highlights: Review on electrical energy storage (EES) degradation for power system analysis. An optimal operation regime is devised for the photovoltaic/biogas/EES system. Levelized cost of electricity for EES is calculated with capacity fade model. LiCoO2 storage is cost competitive at 200 $/kWh mark compared to generators. Abstract: Off-grid renewable energy system is a critical infrastructure in providing electrical power for small communities, especially in remote and rural areas where grid connection points are not available. Due to the diurnal and intermittent nature of solar irradiance, the photovoltaic (PV) power plant can introduce generation and load power imbalance issue. Anaerobic digestion biogas power plant (AD) also has a part-load operation constraint that needs to be met. To overcome these issues, electrical energy storage (EES) such as Graphite/LiCoO2 needs to be employed to provide generation flexibility. The research work provided in this paper is twofold. An optimal operating regime is devised for the PV-AD-EES hybrid system, followed by a study on the levelized cost of electricity (LCOE). Degradation cost per kWh and degradation cost per cycle for EES are considered. 22 years (1994–2015) of irradiance data for Turkwel Gorge Dam, Kenya (1.90°N, 35.34°E) and the Kenya national load are used for the study. With the current technology costs and a discount rate at 8%, it is shown that the capital cost for LiCoO2 needs to be reduced to 200 $/kWh to be economically competitive with dispatchable source such as AD biogas power plant by considering the EES degradation costs.